A Carta da População de Portugal (1929): um contributo para a história da cartografia temática em Portugal - Fernandes, Mário (2016)
The heritage cartographic of a country runs unusual ways and, sometimes, the documents emerge were we not expectingthem and adding us unsuspected teachings. The Carta da População de Portugal, 1929 and of the engineer ConstantinoCabral, existing at the Parque Biológico de Vila Nova de Gaia (Biological Park of Vila Nova de Gaia), presented and analyzedhere, was constructed from sheets of Carta Corographica do Reino, with scale 1:100.000, and is an important contribution tothe history of Thematic Cartography in Portugal, being integrated in the representations of absolute values of the populationof country, which began to emerge at this time to responsibility of academic geographers.